If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -3) + 5x + -2 = 10x + 3 + 4 Reorder the terms: 2(-3 + x) + 5x + -2 = 10x + 3 + 4 (-3 * 2 + x * 2) + 5x + -2 = 10x + 3 + 4 (-6 + 2x) + 5x + -2 = 10x + 3 + 4 Reorder the terms: -6 + -2 + 2x + 5x = 10x + 3 + 4 Combine like terms: -6 + -2 = -8 -8 + 2x + 5x = 10x + 3 + 4 Combine like terms: 2x + 5x = 7x -8 + 7x = 10x + 3 + 4 Reorder the terms: -8 + 7x = 3 + 4 + 10x Combine like terms: 3 + 4 = 7 -8 + 7x = 7 + 10x Solving -8 + 7x = 7 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -8 + 7x + -10x = 7 + 10x + -10x Combine like terms: 7x + -10x = -3x -8 + -3x = 7 + 10x + -10x Combine like terms: 10x + -10x = 0 -8 + -3x = 7 + 0 -8 + -3x = 7 Add '8' to each side of the equation. -8 + 8 + -3x = 7 + 8 Combine like terms: -8 + 8 = 0 0 + -3x = 7 + 8 -3x = 7 + 8 Combine like terms: 7 + 8 = 15 -3x = 15 Divide each side by '-3'. x = -5 Simplifying x = -5
| .5x-2.8=.7 | | 7n-1.1=6 | | X-4y=31 | | 7w+1w-15=17 | | 1.3z+1.5=54 | | x^2+8=70 | | 138.24+25x=173.61 | | -5(6y-4)y=-2(y-5) | | y=2(3x-1)-13 | | 7(x-4)2-18=18 | | 12=x-33.25 | | 7m-13-9m=-10 | | F(x)=6x^4+4x^3-x^2-5x-7 | | -30y= | | 7p-9=10 | | y=2(3x-1)+7 | | y-9+3=9y+5 | | 36y=5 | | 3*3+x=4/5(6*7) | | 3n+4=7.3 | | 5p-3=-11+2(p+2) | | .25(28-3t)=14 | | 24a+9= | | 3b+1b+8=4 | | 6(5x-1)=30x-6 | | -3(3p+4)-2(1-14p)=3(5+6p) | | 13=-5x+167 | | 6a+9=12-7(a+4) | | .14(y-7)+.06y=.10y-1.5 | | 18+38=7w | | 4y^7+6y^6-10y^5=0 | | 11+7=a+11 |